Differentiate the functions using the chain rule.
$\displaystyle g(x) = 2(x^3 - 1 )(3x^2 +1)^4$
I have no idea how to use chain rule in this question..Please help !
Begin by using the product rule
Let $\displaystyle u=2(x^3 - 1)$ and $\displaystyle v=(3x^2 +1)^4$
You can find $\displaystyle \frac{du}{dx}$ easily
Use the chain rule for finding $\displaystyle \frac{dv}{dx}$
Let $\displaystyle w=3x^2 +1$ so that $\displaystyle v=w^4$
To find $\displaystyle \frac{dv}{dx}$ use the chain rule which states that $\displaystyle \frac{dv}{dx}=\frac{dv}{dw}\frac{dw}{dx}$
Take a look at this solution.